GEDUNG ORKESTRA DI MAKASSAR DENGAN PENDEKATAN ARSITEKTUR FUTURISTIK - Akbar, Muhammad Ali; Marwati, Marwati (Nature : National Academic Journal of Architecture, 2015)
Orchestral music could be a new color for the type of music that exist, especially in Makassar, so as to provide knowledge and understanding of orchestral music for the community and lovers of music, so the need for container for orchestral music performances and educational tool for the public in Makassar. Another factor affecting the emergence of the idea to plan the building Orchestra is due to increase public interest in the art of classical music that needs to be supported with container musical performances are adequate considering the sound / acoustics, stage design and lighting in the design, so that the message expressed renderer art can be caught well in order to achieve optimum performance quality and satisfaction for the audience. Based on the above conditions produces a phenomenon that in Makassar requires a means lug activities pengaktualisasian art, especially for orchestral music that has a character in accordance with the development of science and technology in modern times, according to the futuristic concept in line with the development of technology which with the rapid advancement of technology then the existence of man-made futuristic it also will grow. Futuristic is an attempt to create a better future. Thought to be a futuristic itself far more creative and innovative in the future and far ahead of his time, so as to create a building that is not only environmentally friendly, but do not rule out the aesthetic values so as to create the impression of a comfortable and safe.